1985
DOI: 10.1038/314534a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of guanine nucleotide binding protein in the activation of polyphosphoinositide phosphodiesterase

Abstract: Interaction of ligands with 'Ca2+-mobilizing' receptors is thought to result in the generation of two second messengers, inositol trisphosphate and diacylglycerol, from a common substrate, phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2) (refs 1, 2), a component of plasma membranes. It is not known how the occupation of such receptors is translated into the activation of the catalytic unit polyphosphoinositide (PPI) phosphodiesterase, and then to cellular activation, but our recent experiments suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
316
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 936 publications
(330 citation statements)
references
References 23 publications
11
316
3
Order By: Relevance
“…Stimulation of inositol lipid hydrolysis by guanine nucleotides compatible with involvement of G proteins in the activity of neutrophil PLC has been described by many investigators [8][9][10][29][30][31][32]. In our hands, the activity of neutlophil cytosolic PLC assayed in lipid vesicles or in heat-inactivated membranes devoid of active G proteins was not affected by GTPyS (Table Ill).…”
Section: Discussionsupporting
confidence: 68%
“…Stimulation of inositol lipid hydrolysis by guanine nucleotides compatible with involvement of G proteins in the activity of neutrophil PLC has been described by many investigators [8][9][10][29][30][31][32]. In our hands, the activity of neutlophil cytosolic PLC assayed in lipid vesicles or in heat-inactivated membranes devoid of active G proteins was not affected by GTPyS (Table Ill).…”
Section: Discussionsupporting
confidence: 68%
“…Other investigators have demonstrated that either GTP or the non-hydrolyzable GTP analogue, GTP-& could stimulate the breakdown of PIP2 to form IP, in either cultured smooth muscle cell membranes [18] or in the homogenate of canine coronary arteries 1191. Similar studies have demonstrated that GTPyS could stimulate the breakdown of PIP2 in either permeable cells or membranes from a variety of tissues [7,8]. These experiments indicate that one or more G proteins most likely mediate the action of a contractile agonist on phospholipase C directly.…”
Section: Discussionsupporting
confidence: 65%
“…In this respect it is worth comparing the rate of PI kinase of 10 mU/mg protein with that of PIP kinase of 0.4 mU/mg protein (both calculated from the present study). This would mean that PIP kinase represents the rate limiting step during the formation of PIP2, and that an activation of this step, through an increase of PIPz, might exert control on phospholipase C. That the substrate supply for phospholipase C is limited and that the inositol lipid kinases may therefore be under separate control have also been discussed elsewhere [11]. Previous findings from this laboratory that insulin activates phospholipase C in fat cells [10] seem to have been confirmed recently [12,13].…”
Section: Resuli"s and Discussionmentioning
confidence: 99%